Evaluation of COVID-19 Patient Safety Compared to Non-COVID-19 Patients and Predisposing Factors of Nursing Errors - Leila Mohammadnahal; Abasat Mirzaei; Mohammad Javad Khezeli (Universidad de La Sabana, 2022)
Objectives: The present study aims to determine Patient Safety in hospitalized patients with COVID-19 compared to non-COVID-19 ones and find predisposing factors of nursing errors according to nurses' perceptions. Methods: This descriptive-comparative research employed data from 800 nurses in eight Iranian hospitals in 2021 using three researcher-made questionnaires of sociodemographic, patient safety indicators, and predisposing factors of nursing errors, with high reliability and validity. The collected data were analyzed using ANOVA, independent t-test, and the SPSS22 software. Results: The mean patient safety scores in patients with and without COVID-19 were 3.42 ± 0.17 and 3.74 ± 0.06, respectively. The highest differences in patient safety were attributed to infection control (0.66) and patient fall (0.56) dimensions. The most common causes of nursing errors were related to management (2.67 ± 1.39), and the most common predisposing factors of nursing errors were high workload, low ratio of nurses to patients, and fatigue. Conclusions: COVID-19 patients have lower safety than non-COVID ones. Also, improper management and high workload lead to nursing errors. Therefore, the authorities must devise appropriate strategies to reduce the nurses' workload and improve patient safety, especially in COVID-19 patients.